Modelagem para avaliação de locais adequados para a instalação de usinas fotovoltaicas - Rediske, Graciele (2019)
Solar energy plays an important role in the evolution of the participation of alternative sources in the world energy matrix. Brazil has good conditions for the exploitation of this energy source, due to the good geographic location for the generation of energy through the sun, falling prices of photovoltaic equipment and increase of tariffs. Consequently, investing in photovoltaic plants demonstrates attractiveness to investors. Although photovoltaic energy presents several advantages, being an opportunity to aggregate more scale to the ventures, some points must be observed in the moment of implementing new projects of solar plants. The feasibility and attractiveness of the project depends on the location of the plant, so the choice of this must occur well before receiving investments, since many factors play an important role at the time of this choice. The decision to install photovoltaic power plants is a critical issue for large-scale projects due to climatic aspects, proximity to facilities and the presence of protected environmental areas. The objective of this study is to propose a model capable of indicating the best location for implantation of large scale photovoltaic projects in the Brazilian territory. In the proposed modeling, the relevant factors to be considered in the choice of the ideal site were determined, and the tools of Geographic Information System (GIS), supported by methods Multicriteria Decision Aid (MCDA), were combined. The analysis of the areas was performed within the gvSig software, using AHP methods for factor weighting and TOPSIS for the ranking of alternatives. The modeling was applied in the Santa Cruz do Sul microregion, which covers 16 municipalities in the state of Rio Grande do Sul, located in the Southern Region of Brazil, which has a total area of 5.564 km². The spatial fitness index was calculated for the whole territory of the study scenario. A total of 453 areas were identified that could receive a large photovoltaic installation, equivalent to 1823,35 km2 of the study scenario. In addition to the geographic distribution of suitable areas, this study also performed the classification of suitable areas, representing its capacity in 4 categories: improper, good, very good and excellent. The greatest potential for photovoltaic systems is observed for the sites in the southern part of the Santa Cruz do Sul microregion, where the largest plots of these areas are located in the municipalities of Venâncio Aires, Vera Cruz and Santa Cruz do Sul. The modeling proposed in this document combining SIG-MCDM is applicable to similar investigations in other regions and to assess the spatial adequacy of other renewable energy technologies.